Vaginal Length After Laparoscopic Versus Vaginal Closure: A Randomized Trial [1K]. (May 2016) - Nezhat, Camran; Kakar, Freshta; Nezhat, Azadeh; Seagle, Brandon; Grace, Lindsey; Main, Jillian
Abstract : INTRODUCTION: Despite the increasing numbers of total laparoscopic hysterectomies (TLH) being performed each year, randomized comparisons between laparoscopic versus vaginal cuff closure are lacking. The purpose of this study is to determine the change in vaginal length after TLH with laparoscopic cuff closure (LC) versus vaginal cuff closure (VC). METHODS: Randomized study of women undergoing TLH. Vaginal length was measured pre-operatively and then 6–12 weeks and 6–12 months postoperatively. The primary outcome was change in vaginal length. Secondary outcomes were vaginal vault dehiscence and cuff closure operative time. Analysis was per-protocol using Mann-Whitney U test and Wilcoxon signed rank test. RESULTS: 68 patients were randomized, 34 patients were excluded due to inadequate follow-up, malignancy or alternative closure. No significant differences in age, BMI or parity were found. The median preoperative vaginal lengths were similar: LC 9.0 cm vs VC 9.25 cm; P =.23. The difference in median vaginal lengths at 6–12 weeks were: LC 9.0 cm versus VC 8.9 cm ( P =.68). The median vaginal lengths at 6–12 months were both 9.5 cm ( P =.94). When compared to the preoperative lengths, there were no significant differences at the 6–12 evaluation. The cuff closure time was significantly longer in the LC group (20 min versus 8 minutes, P <.05). There were no cases of vaginal cuff dehiscence. CONCLUSION: After total laparoscopic hysterectomy, the vaginal length at 12 months did not differ based on method of vaginal closure. Laparoscopic cuff closure times are longer than vaginal cuff closures and neither method had cases of vaginal cuff dehiscence.